2018
DOI: 10.1039/c8ra00497h
|View full text |Cite
|
Sign up to set email alerts
|

Laser induced graphitization of PAN-based carbon fibers

Abstract: A new method based on laser technique is proposed to graphitize PAN-based CFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…The precursor for carbon fiber today is polyacrylonitrile (PAN), and lignin has the potential to be used as an alternative to PAN in order to make the process a lot cheaper. Carbon fibers already have a wide range of applications, such as automobile industry, civil engineering, aircrafts and sport goods [35,36]. Activated carbons are characterized by their surface area and size of pores, and are great adsorbents of organic and inorganic substances.…”
Section: Introductionmentioning
confidence: 99%
“…The precursor for carbon fiber today is polyacrylonitrile (PAN), and lignin has the potential to be used as an alternative to PAN in order to make the process a lot cheaper. Carbon fibers already have a wide range of applications, such as automobile industry, civil engineering, aircrafts and sport goods [35,36]. Activated carbons are characterized by their surface area and size of pores, and are great adsorbents of organic and inorganic substances.…”
Section: Introductionmentioning
confidence: 99%
“…This method combines large-area graphene preparation and patterning with a single fabrication step without the need for expensive cleanroom equipment, wet chemical steps, reducing agents, solvents, subsequent treatments, or other supporting processes. This laser-induced graphene (LIG) has stimulated research in many areas, ranging from fundamental to applied sciences, investigating the laser graphitization process [41][42][43], effects of various lasers [44][45][46], environments [47,48], and lasing parameters [49][50][51], to the development of a large variety of flexible physical and chemical sensors. The latter utilizes LIG as an electrochemical transducer while incorporating additional chemical recognition systems and surface functionalization to interact with analytic molecules [52][53][54], such as glucose [55], tyrosine [56], dopamine [57], bisphenol [53], thrombin [58], ascorbic and uric acid [56].…”
mentioning
confidence: 99%
“…Malard et al have shown that the D ' band is independent of the edge structure; in other words, it is caused by defects in the internal structure. The I D /I G value is commonly considered as a rule of the defect concentration in graphite materials . In this study, we define the I D ’ /I G value as the defect concentration in the internal structure of carbon fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy was also utilized to investigate the chemical structure changes of HMCF during anodization. As shown in 19,20 In this study, we define the I D' /I G value as the defect concentration in the internal structure of carbon fibers. As shown in Figure 8B, it can be clearly found that the I D /I G value of HMCF-a is a little raise compared with that of untreated HMCF, while the I D /I G value of HMCF-aa is much higher than that of HMCF.…”
Section: Itmentioning
confidence: 99%